Pengaruh Model Pembelajaran TGT (Teams Games Tournament) Terhadap Hasil Belajar Tenis Meja - Andrijanto, Dony (Indonesian Journal of Physical Education and Sport Science, 2023)
Study Purpose. The success of the learning process depends on the educator, where an educator plays an important role in the learning process. This study aimed to determine the effect of learning media on the learning achievement of forehand strokes in table tennis games. Materials and Methods. The method used in this research was a quasi-experimental research with one group pre-test post-test design. The population used in this study were students in MTS Sunan Giri class VIII the sample used was 36 students. The research was conducted 4 times. The data collection technique used was a table tennis forehand test. The analysis technique used was descriptive analysis, normality test, and hypothesis testing. Results. There was an effect of learning media on the learning achievement of forehand shots in table tennis games. this is evidenced by the t-test results obtained of 0.00 which means a significant value <0.05. Conclussion.Through these results, it can be concluded that there was a significant influence of learning media on the learning achievements of forehand strokes in table tennis games.